Nutritional Supplementation Concurrent with Nutrition Education Accelerates the Wound Healing Process in Patients with Diabetic Foot Ulcers - Basiri, Raedeh (Biomedicines, 2020)
Trials on nutritional supplements for the treatment of diabetic foot ulcer (DFU) have only evaluated the effects of supplementation with specific nutrients. Additionally, nutrition education has not been a systematic part of these studies. The aim of this study was to evaluate the effects of a nutrient-dense formula combined with nutrition education on wound healing in DFU patients. Twenty-nine patients were randomly assigned to the treatment group (n = 15) receiving two servings of supplements daily plus nutrition education or control group (n = 14) that received the standard of care but no additional nutritional or educational intervention. Both groups were followed for a maximum of 12 weeks. Wound healing, as measured by planimetry, was examined at baseline and every four weeks until complete wound closure or up to 12 weeks. There were no significant differences between groups for BMI, age, duration of diabetes, wound age estimation, or wound area at baseline. The treatment group experienced a faster wound healing rate (6.43 mm(2)/week more reduction in the wound area) than the control group. The mean reduction in the wound area during the first four weeks of the study was almost 13-fold greater in the treatment group compared to the control group (18.0 mm(2)/week vs. 1.4 mm(2)/week, respectively). Our findings showed that nutrition supplementation plus nutrition education significantly accelerated wound healing in DFU patients compared to those who just received a standard-of-care regimen.